Answered

Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

PLEASE HELP!!!!!!!!!!!!!!!!!!!!!1111 I REALLY NEED HELP I A, BEGGIN YOU GUYS!!!!!!!!!!!!!!!!!!!!!!!!!!! ILL GIVE BRAINLIEST AND EXTRA POINTS!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

PLEASE HELP1111 I REALLY NEED HELP I A BEGGIN YOU GUYS ILL GIVE BRAINLIEST AND EXTRA POINTS class=

Sagot :

Answer:

Step-by-step explanation:

4y - 2(5 - y + 4) = 4y - 2(9 - y)

                         = 4y + 9*(-2) - y *(-2)

                         = 4y  - 18 + 2y      {Combine like terms 4y and 2y}

                         = 6y - 18

6y - 18 = 6*y - 6*3

           = 6(y - 3)

6y- 18 =  2 *3y - 2*9

          = 2(3y -9)

2(3y - 9) and 6(y- 3 ) are equivalent to 4y - 2(5- y +4)

Others are not equivalent